2024
DOI: 10.1021/acs.jmedchem.3c01979
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Activation a Promise in Drug Development? New Insights into SIRT3 Biology and Its Implications on the Drug Discovery Process

Chiara Lambona,
Clemens Zwergel,
Sergio Valente
et al.

Abstract: Sirtuins catalyze deacetylation of lysine residues with a NAD + -dependent mechanism. In mammals, the sirtuin family is composed of seven members, divided into four subclasses that differ in substrate specificity, subcellular localization, regulation, as well as interactions with other proteins, both within and outside the epigenetic field. Recently, much interest has been growing in SIRT3, which is mainly involved in regulating mitochondrial metabolism. Moreover, SIRT3 seems to be protective in diseases such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 265 publications
0
5
0
Order By: Relevance
“…In 2020, a series of benzothieno [3,2-d]pyrimidines, which are active as anticancer agents from a large screening performed by National Cancer Institute (NCI, USA), was investigated by Khalil [131]. Novel derivatives have been designed by modifying the tetrahydrobenzo [4,5]thieno [2,3-d]pyrimidine scaffold, which has previously resulted in active antiproliferative agents. This was conducted to study the effect of chemical modifications and to explore thieno [2,3-d]pyrimidines as a potent SIRTI.…”
Section: Design Of Dual Sirt1/2ismentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, a series of benzothieno [3,2-d]pyrimidines, which are active as anticancer agents from a large screening performed by National Cancer Institute (NCI, USA), was investigated by Khalil [131]. Novel derivatives have been designed by modifying the tetrahydrobenzo [4,5]thieno [2,3-d]pyrimidine scaffold, which has previously resulted in active antiproliferative agents. This was conducted to study the effect of chemical modifications and to explore thieno [2,3-d]pyrimidines as a potent SIRTI.…”
Section: Design Of Dual Sirt1/2ismentioning
confidence: 99%
“…Extensive research has already been conducted on SIRT1 modulators, but also on SIRT2 [2,3], SIRT3 [4], and SIRT6 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…SIRTs, particularly SIRT3, are also associated with mitochondrial dysfunction, altered NAD + /NADPH ratio, and increased reactive oxygen species (ROS) [ 38 ]. Increased expression of NADPH oxidase 4 (NOX4) has been reported in the lungs of patients with IPF, which may be key to modulating profibrotic signaling [ 39 ].…”
Section: Sirtuins In Idiopathic Pulmonary Fibrosis: Focus On Putative...mentioning
confidence: 99%
“…Precise modulation of mitochondrial function has been demonstrated to alleviate myocardial injury and preserve cardiac function. Acetylation, a central player in mitochondrial protein homeostasis, is particularly relevant, with Sirtuin 3 (SIRT3), a NAD+-dependent deacetylase among the seven mammalian sirtuins (SIRT1–7). Notably, SIRT3, alongside SIRT4 and SIRT5, localizes within mitochondria, distinguishing them from counterparts in the nucleus or cytoplasm. Research indicates that SIRT3, abundantly expressed in healthy hearts, exhibits robust deacetylase activity compared to the weaker activities of SIRT4 and SIRT5. , The primary deacetylation targets of SIRT3 encompass mitochondrial proteins predominantly associated with energy metabolism, redox balance, and mitochondrial dynamics. Through the regulation of acetylation in these proteins, SIRT3 protects mitochondria from damage and dysfunction, thereby hindering the onset of various CVDs, cancer, and age-related diseases. , …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed the downregulation of SIRT3 in diverse cardiopathological conditions, with its overexpression demonstrating the potential to mitigate a spectrum of cardiopathological phenomena. SIRT3 expression exhibits variability under different physiological factors, including age, diet, and exercise . Notably, exercise has a positive influence on SIRT3 expression in the heart, and SIRT3 is the sole sirtuin found to decrease with age. , Recognizing the pivotal role of SIRT3 in cardiovascular diseases, the modulation of SIRT3 levels emerges as a promising therapeutic strategy to protect against cardiovascular diseases. ,,, Several SIRT3 activators, capable of eliciting SIRT3 expression or enhancing its biochemical activity, such as metformin, and others, along with natural products like resveratrol, honokiol, berberine, and salidroside, have been reported to exhibit therapeutic potential for various CVDs. ,,, Vigorous efforts to discover new SIRT3 activators with potent activity, good selectivity, and high bioavailability hold great promise for the exploration of novel therapies for CVDs.…”
Section: Introductionmentioning
confidence: 99%